ASPECTE GEOLOGICE ŞI HIDROGEOLOGICE ALE COMPLEXULUI ISTORICO-NATURAL „ORHEIUL VECHI” - Boboc, Nicolae; Chirică, Lazăr; Castraveţ, Tudor (CEP USM, 2007)
This article includes an analysis of geological and hydrological structure of the historical and natural complex “Orheiul Vechi” and the information obtained from the investigation of the region in recent years.
Keywords: complexul istorico-natural „Orheiul Vechi ”; specificul hidrogeologic